Complexity, leadership, and megaproject performance: A configuration analysis - Retno Damayanti; Budi Hartono; Andi Wijaya (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Rapid worldwide growth in megaprojects has attracted academic interest. In practice, complexity is one of the main causes for the failure of megaprojects. This study proposes a system of project manager leadership to overcome problems of complexity in achieving success with a megaproject. Design/methodology/approach: This study uses configuration analysis, fuzzy-set qualitative comparative analysis (fsQCA), to investigate the combination of complexity and leadership competencies that promote megaproject success. This study analyzes three megaproject manager leadership competencies-technical, emotional-social and adaptive-with three megaproject complexities-structural, social and emergent-to determine the combinations and levels required to ensure a megaproject's short- and long-term success. Seven Indonesian infrastructure megaprojects were involved in this explorative study. Findings: This study has identified four combinations between complexity and leadership competencies and three necessary conditions that can lead to a successful megaproject. This study also reports that insufficient project manager leadership competence in the technical, emotional-social, and adaptive aspects can lead to lower megaproject performance. Research limitations/implications: By using fsQCA, this study is sufficient to understand the combination of complexity and leadership competencies in the megaproject performance. However, configuration comparative analysis using small samples is unable to explain results that are more rigorous when compared with the statistical approach. Having higher cases and additional analytical approaches that can lead to a more robust quantitative analysis method is strongly needed to address these limitations. Practical implications: For practitioners, this study proposes effective leadership competency combinations for managing various complexities of the megaproject. Originality/value: This study provides an insight into the competencies of megaproject management leadership. This study contributes to the literature by providing fresh perspectives on megaproject management, especially in terms of complexity and leadership. This is an important research area for the development of megaproject management theory as it fills theoretical gaps in megaproject management in terms of the leadership aspect.
Keywords: 650; Complexity; configuration analysis; leadership; megaproject performance